(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
Deep learning-based artificial intelligence (AI) can solve real-world problems in all fields, including medicine and dentistry. This study conducts a literature review focusing on oral and craniofacial radiology deep learning.